Agricultural and Forestry Reconstruction After the Great East Japan Earthquake - Monma, Toshiyuki; Goto, Itsuo; Hayashi, Takahisa; Tachiya, Hidekiyo; Ohsawa, Kanju (Springer Nature, 2015)
Effects of Radiation / Radiation Protection